2013
DOI: 10.1016/j.earlhumdev.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal neurobehavioral abnormalities and MRI brain injury in encephalopathic newborns treated with hypothermia

Abstract: Background Neonatal Encephalopathy (NE) is a prominent cause of infant mortality and neurodevelopmental disability. Hypothermia is an effective neuroprotective therapy for newborns with encephalopathy. Post-hypothermia functional-anatomical correlation between neonatal neurobehavioral abnormalities and brain injury findings on MRI in encephalopathic newborns has not been previously described. Aim To evaluate the relationship between neonatal neurobehavioral abnormalities and brain injury on magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
(25 reference statements)
2
14
0
1
Order By: Relevance
“…The two neonates who had normal early MRI but abnormal late MRI had normal signal intensity within the PLIC on both [30][31][32][33]. The good agreement between early and late MRI findings in our study suggests that early MRI might be helpful for managing intensive-care treatment when the hypothermia treatment ends (day 4).…”
Section: Signal Changes In the Posterior Limb Of Internal Capsule (Plic)supporting
confidence: 65%
“…The two neonates who had normal early MRI but abnormal late MRI had normal signal intensity within the PLIC on both [30][31][32][33]. The good agreement between early and late MRI findings in our study suggests that early MRI might be helpful for managing intensive-care treatment when the hypothermia treatment ends (day 4).…”
Section: Signal Changes In the Posterior Limb Of Internal Capsule (Plic)supporting
confidence: 65%
“…This is concurrent with other findings using the NNNS assessment, where different NNNS summary scores have been associated with unique and specific epigenetic patterning 10,11,13,41,42 or factors from the prenatal environment. [20][21][22][23][24][25][26][27] Quality of movement and infant attention were associated with methylation of genes involving neurological development and function, including neurotransmitter uptake, dopamine uptake involved in synaptic transmission, and dendritic spine organization. The placenta is an endocrine organ that expresses similar neuropeptides to the human brain, 43 and previous studies have identified associations between methylation of genes that are expressed within the human brain, such as the serotonin receptor HTR2A.…”
Section: Discussionmentioning
confidence: 99%
“…16 This assessment has established validity in identifying high-risk infants and predicting later life health outcomes. [17][18][19][20][21][22][23][24][25][26][27][28] The cohort examined in this study represents a relatively healthy population, and the maternal environment experienced by these infants is likely similar to the population at large. These results suggest that there is an underlying level of variation in behavioral phenotypes as well as a level of epigenetic variation in the placenta of otherwise healthy infants, and that in some cases the variation in the placenta is related to the variation observed in neurobehavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported the use of the NNNS for quantitatively documenting neurological status in newborns with HIE after therapeutic hypothermia (8). While we observed a significant relationship between NNNS motor abnormalities and severe brain injury by conventional MRI, we seek to extend this work by further examining brain structural-anatomical correlations using more robust quantitative MRI methods.…”
Section: Introductionmentioning
confidence: 99%